(untitled) (Research, Society and Development, 2021)
The parts that make up the guitar are made of the most varied materials to meet the needs related to each component, according to their specific functions to be performed on the instrument. One of the important aspects of current research in musical acoustics is the connection of the measurable physical properties of a musical instrument and its sound or tonal quality. The processing of acoustic signals from a string instrument, for example, can correlate the acoustic signals or sounds of the guitar with a mathematical operation of convolution or deconvolution by establishing relationships with its physical properties. Another technique used is to obtain responses in terms of frequency of vibration or time domain and the impulse excitation technique. The present work aims to evaluate through the separation of the signal referring to the frequency response of the guitar through the deconvolution of the sound signal generated when playing the instrument by the string signal recorded separately. It also seeks to establish the relationships with the responses obtained through the impulse excitation technique. And the results show that these two techniques can represent important techniques for characterizing materials used in string instruments such as the guitar.